2016
DOI: 10.1002/2016jf004039
|View full text |Cite
|
Sign up to set email alerts
|

A physically based 3‐D model of ice cliff evolution over debris‐covered glaciers

Abstract: We use high‐resolution digital elevation models (DEMs) from unmanned aerial vehicle (UAV) surveys to document the evolution of four ice cliffs on the debris‐covered tongue of Lirung Glacier, Nepal, over one ablation season. Observations show that out of four cliffs, three different patterns of evolution emerge: (i) reclining cliffs that flatten during the ablation season; (ii) stable cliffs that maintain a self‐similar geometry; and (iii) growing cliffs, expanding laterally. We use the insights from this uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 54 publications
7
114
0
Order By: Relevance
“…Pond I (Figure 7) was also not observed in detail in May 2013, but appeared in the UAV orthophoto as a pond of moderate size (740 m 2 , which would possibly be observable by Landsat) with an adjacent ice cliff with a fairly uniform slope angle, and no vertical or overhanging face (Figure 7a-c; Cliff 4 in Brun et al, 2016;Buri et al, 2016). The pond shrank slightly in area to 550 m 2 by October 2013 (Figure 7), and the pond outline translated ∼10.5 m to the east (local glacier surface velocity is ∼3 m a −1 to the southeast).…”
Section: Changes At Ponds 2013mentioning
confidence: 99%
“…Pond I (Figure 7) was also not observed in detail in May 2013, but appeared in the UAV orthophoto as a pond of moderate size (740 m 2 , which would possibly be observable by Landsat) with an adjacent ice cliff with a fairly uniform slope angle, and no vertical or overhanging face (Figure 7a-c; Cliff 4 in Brun et al, 2016;Buri et al, 2016). The pond shrank slightly in area to 550 m 2 by October 2013 (Figure 7), and the pond outline translated ∼10.5 m to the east (local glacier surface velocity is ∼3 m a −1 to the southeast).…”
Section: Changes At Ponds 2013mentioning
confidence: 99%
“…As ablation at ice cliffs is rapid, in the case of Ngozumpa glacier accounting for 40% of volume losses over the lower part of the glacier tongue (Thompson and others, 2016), repeat analysis of high-resolution photographic DSMs over time, that have been used to monitor ice cliff backwasting (e.g. Brun and others, 2016;Buri and others, 2016), would also reveal the spatial distribution of debris thickness behind the ice cliffs in the form of a time-space substitution. More extensive measurements of the underlying ice surface and debris thickness using high frequency GPR (McCarthy and others, 2017) offers a useful tool for determining relationships between surface terrain and underlying terrain that can be expected to offer valuable information in determining the validity of the assumption of horizontal extension of the debris/ ice interface applied in this study.…”
Section: Evaluation Of the Utility Of Sfm-mvs Dsms For Determining Sumentioning
confidence: 99%
“…High-resolution photographic DSMs have already been generated for debris-covered glaciers and used to characterize the glacier surface (Kraaijenbrink and others, 2016), measure displacements of the glacier surface (Immerzeel and others, 2014) and monitor changes in ice cliffs (Brun and others, 2016;Buri and others, 2016). In this paper we (i) present a workflow to quantify debris thickness exposed above ice cliffs using measurements from scaled, high-resolution photographic DSMs, (ii) compare the derived debris thickness to available debris thickness collected by alternative means and (iii) discuss the utility and limitations of the new method of determining supraglacial debris thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism(s) of ice cliff formation, the controls of ice cliff migration patterns and ice cliff residence time on a glacier are gaining research attention but are still poorly understood processes, in part, due to a lack of base data (Reid and Brock, 2014;Watson et al, 2017). Melt and surface energy fluxes at specific ice cliffs have been studied in detail (Sakai et al, 1998;Han et al, 2010;Sakai et al, 2002;Reid and Brock, 2014;Buri et al, 2016a) and digital elevation model (DEM) differencing has shown the spatial trends of enhanced glacier melt relative to surrounding debris cover and ice cliff evolution at the scale of several cliffs or a single glacier tongue (Thompson et al, 2016;Brun et al, 2016). All of the studies mentioned suggest that ice cliffs, if present on a debris-covered glacier, need to be accounted for in order to adequately model glacier mass loss and response to climate.…”
Section: Introductionmentioning
confidence: 99%